Awareness and intention to use event‐driven and long‐acting injectable pre‐exposure prophylaxis among adolescent and young men who have sex with men and transgender women in Brazil: a cross‐sectional study - Laio Magno; Beo Oliveira Leite; Alexandre Grangeiro; Lorenza Dezanet; Fabiane Soares; Inês Dourado (Journal of the International AIDS Society, 2025)
Abstract Introduction New pre‐exposure prophylaxis (PrEP) options, including event‐driven and long‐acting injectable, may enhance HIV prevention strategies among adolescents and youth. This study examined awareness and intention to use event‐driven and long‐acting injectable PrEP, along with associated factors, among adolescent and young men who have sex with men and transgender women. Methods A cross‐sectional study was conducted between December 2020 and February 2022 among men who have sex with men and young transgender women aged 15–20 years, who participated in a daily oral PrEP cohort study in Salvador and São Paulo, Brazil. Binomial logistic regression models analysed factors associated with the intention to use event‐driven and long‐acting injectable PrEP. Results A total of 1221 participants were enrolled in the cohort at the time of this analysis, with 597 responding to the survey. Awareness of event‐driven and long‐acting injectable PrEP was reported by 15.3% and 18.0% of participants, respectively. Intention to use event‐driven PrEP was reported by 56.4% of participants, while 81.5% expressed intention to use long‐acting injectable PrEP. Participants with lower and moderate adherence to daily oral PrEP were more likely to intend to use event‐driven PrEP (OR = 1.79; 95% CI: 1.04–3.08), whereas those who reported always or often using condoms in insertive anal sex with steady or casual partners were less likely to intend to use event‐driven PrEP (OR = 0.37; 95% CI: 0.15–0.90). For long‐acting injectable PrEP, participants with middle (OR = 1.93; 95% CI: 1.05–3.53) or low socio‐economic status (OR = 3.13; 95% CI: 1.30–7.51) and those reporting three or more casual partners in the past 3 months (OR = 2.25; 95% CI: 1.30–3.89) were more likely to intend to use long‐acting injectable PrEP. Conversely, participants who had never used daily oral PrEP were less likely to intend to use long‐acting injectable PrEP (OR = 0.31; 95% CI: 0.11–0.92). Conclusions Adolescents and young people in Brazil demonstrated a stronger preference for long‐acting injectable over event‐driven PrEP, with sexual behaviour patterns significantly influencing choices. Expanding prevention options may enhance PrEP uptake and adherence, improving HIV prevention strategies among adolescents and young adults.